2020
DOI: 10.32491/jii.v20i2.523
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Celebes rainbowfish, Marosatherina ladigesi Ahl, 1936 in Pattunuang and Batu Puteh Rivers, South Sulawesi

Abstract: Marosatherina ladigesi is one of endemic fishes in South Sulawesi and also as ornamental fish. Anthropogenic activities such as destructive fishing and degradation caused by the dredging of sand carried M. ladigesi to the red list of threatened IUCN category as vulnerable species. Accordingly, conservation efforts are needed to maintenance fish population in its habitat. The biologic information for conservation is reproduction of fishes. This research aimed to described reproduction of Celebes rainbow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In Matano medaka fish (O. matanensis) a greater fecundity was recorded compared to the medaka fish (O. profundicola), with 22-180 eggs (Eragradhini, 2020). The occurrence of low fecundity in a fish species is thought to be related to its small body shape, as is the case with the beseng-beseng fish in the Maros River (Jayadi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In Matano medaka fish (O. matanensis) a greater fecundity was recorded compared to the medaka fish (O. profundicola), with 22-180 eggs (Eragradhini, 2020). The occurrence of low fecundity in a fish species is thought to be related to its small body shape, as is the case with the beseng-beseng fish in the Maros River (Jayadi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Matano medaka fish (O. matanensis) found greater fecundity than medaka fish (O. profundicola), namely 22-180 eggs (Eragradhini, 2020). The occurrence of low fecundity in a fish species _______________________________________________________________________________ is thought to be related to its small body shape, as is the case with the beseng-beseng fish in the Maros River (Jayadi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The IKG value of the endemic bonti-bonti fish in Lake Towuti is relatively small for male fish compared to female fish (Andy Omar et al, 2012;Nasution et al, 2010). The IKG value of female beseng-beseng fish is greater than the IKG value of males (Jayadi et al, 2016). The IKG value of female Glossogobius giuris fish is higher than that of males in Lake Limboto (Juliana et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the fish body, mortality is affected by differences in age and ability to adapt to the environment. Meanwhile, the external factors include abiotic conditions, competition between species, lack of food, handling, catching, and increasing the number of fish populations in the same space and also heat stress factor (Nasyrah et al 2019). Based on the research, the lowest survival rate was found in the 90% artificial feed treatment group.…”
Section: Survival Ratesmentioning
confidence: 94%